FAKTOR-FAKTOR YANG MEMPENGARUHI BEBAN KERJA ROOM ATTENDANT DI GRAND JATRA HOTEL PEKANBARU - Muthya Achyana; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
One of the factors which have influence to the success level of the organization is employees performance. One of the efforts to improve the employees performance is by giving attention to workload. This research aims to determine factors influence workload of room attendant in Grand Jatra Hotel Pekanbaru.Descriptive quantitative method was used to examine the issues raised. The sampel in this research are 10 peoples and used census method. While the data collection technique in this research used questionnaires, observation, interviews and documentation. A likert scale used as a measure to determine the length of the interval.Based on the research that has been done, to the factors that influence workload of room attendant in Grand Jatra Hotel Pekanbaru are namely external factors and internal factors. Where the eksternal factors that most influence significantly.Keyword : Workload, Room Attendant, Grand Jatra Hotel Pekanbaru